2015
DOI: 10.1542/peds.2014-0620
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Obstructive Sleep Apnea Symptoms After Pediatric Adenotonsillectomy

Abstract: BACKGROUND AND OBJECTIVES: Data from a randomized, controlled study of adenotonsillectomy for obstructive sleep apnea syndrome (OSAS) were used to test the hypothesis that children undergoing surgery had greater quality of life (QoL) and symptom improvement than control subjects. The objectives were to compare changes in validated QoL and symptom measurements among children randomized to undergo adenotonsillectomy or watchful waiting; to determine whether race, weight, or baseline OSAS severity influenced chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 37 publications
(35 reference statements)
7
116
0
7
Order By: Relevance
“…Starting early in life, children with OSAS have increased utilisation of healthcare services, mostly related to respiratory morbidity and thus increased societal costs (class III) [112]. Both generic and disease-specific health-related quality of life measures improve after adenotonsillectomy (class I) [113].…”
Section: Decreased Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Starting early in life, children with OSAS have increased utilisation of healthcare services, mostly related to respiratory morbidity and thus increased societal costs (class III) [112]. Both generic and disease-specific health-related quality of life measures improve after adenotonsillectomy (class I) [113].…”
Section: Decreased Quality Of Lifementioning
confidence: 99%
“…In the CHAT study, changes in the attention and executive function objective scores from baseline to follow-up did not differ between the early-adenotonsillectomy and the watchful-waiting study groups (class I) [126]. However, there was a significant improvement in executive functioning, attention, behaviour and excessive daytime sleepiness as rated by parents, which was predicted by the preoperative severity of symptoms but not by the AHI (class I) [113,177]. Similarly, two systematic reviews of mostly class III and IV studies concluded that adenotonsillectomy is followed by improvements in behavioural problems and neurocognitive skills irrespective of SDB severity [178,179].…”
mentioning
confidence: 91%
“…27,28 One explanation for these small effects is that sleep-related cognitive weaknesses may be less evident on highly structured tests than under "free-living" conditions in which children have to regulate their own behavior according to environmental demands. 45,46 Other possibilities are that the effects of chronic sleep disturbances on brain function are more difficult to reverse than responses to environmental conditions or that longer follow-up is needed to detect more substantial effects of AT on test performance.…”
mentioning
confidence: 99%
“…It gives a global health overview, and usefully has two forms: the parent proxy report form and the age-specific child self-report form. [49][50][51] Similarly, the KINDL-R questionnaire for measuring health-related QoL in children and adolescents, 60,61 the Child Health Questionnaire ('CHQ') 38,[54][55][56] and the Child Behavior Checklist ('CBCL') 20,21,62 are general patient-reported outcome measures that have different forms for various age groups. These tools have the benefit of age-appropriate questions, but their use would potentially limit comparison of the findings outside of that age group.…”
Section: Discussionmentioning
confidence: 99%